Scientometric Analysis of Ethnomathematics-Based Development: A Systematic Literature Review - Lakapu, Meryani; Djong, Kristoforus Djawa; Uskono, Irmina Veronika; Jagom, Yohanes Ovaritus; Nai, Yustinus Didimus; Savio, Diogo (Jurnal Pendidikan MIPA, 2025)
Ethnomathematics-based research and development play a vital role in connecting cultural heritage with mathematics to enhance students’ understanding and appreciation of mathematical concepts. This study employs a scientometric indicator analysis to explore the development of ethnomathematics-based research from 2014 to 2024. Using bibliometric methods and network visualization via VOSviewer software, 614 articles from Scopus and ProQuest databases were analyzed to examine trends in publication, author profiles, types of developed products, and development model preferences. The findings reveal a steady annual increase in publications, peaking in 2020. Indonesia accounts for 83.33% of the studies, highlighting national dominance. Most articles were authored by lecturers and final-year students, with a primary focus on developing instructional tools such as learning designs and teaching materials (each at 16.67%). The general design model was the most utilized (55.56%), followed by the Plomp and ADDIE models. Limited documentation and the absence of digital versions of local culture-based products were identified as key motivations behind the development efforts. This study also maps keyword co-occurrences and author collaboration networks to visualize the direction of research. The dominance of practical-oriented outputs highlights a need to emphasize evaluation and long-term implementation stages. Moreover, the lack of global contributions suggests the importance of cross-national collaboration to broaden ethnomathematics research perspectives. Overall, this scientometric review offers strategic insights and identifies opportunities to strengthen product design, methodological rigor, and global engagement in ethnomathematics-based education research. Future developments must prioritize standardized evaluation aspects that are rooted in local cultural contexts. In addition, the integration of technology in the form of interactive digital media should be enhanced to meet the needs of 21st-century learning. These findings provide a valuable reference for researchers seeking to design culturally responsive educational products and encourage more collaborative and sustained research in the field of ethnomathematics.   Keywords: scientometric, development, ethnomathematics.